This is what's in your wallet... and how you use it - Tamás Briglevics; Scott Schuh (European Central Bank (ECB), 2014)
Data from the 2012 Diary of Consumer Payment Choice (DCPC) shows substantial changes in payment instrument use of U.S. households compared to the results in Klee (2008) (which were based on data from 2001): Checks have virtually disappeared from purchase transactions, while still play a role in bill payments. Cash, on the other hand, still plays a large role for low-value transactions. The diary data is used to jointly analyse payment instrument use and consumers' demand for liquid assets. Preliminary results indicate that payment instrument choice is an integral part of consumers' cash management practices and hence cash demand; therefore, contrary to simple Baumol (1952)|Tobin (1956) models, they should be analysed together.
Keywords: E41; E42; 330; cash withdrawals; Diary of Consumer Payment Choice; money demand; payment cards; payment instrument choice